Lockdown, quarantine measures, and social distancing: Associations with depression, anxiety and distress at the beginning of the COVID-19 pandemic among adults from Germany. (November 2020) - Benke, Christoph; Autenrieth, Lara K.; Asselmann, Eva; Pané-Farré, Christiane A.
Highlights: sociodemographic and COVID-19 related predictors were related to immediate mental health consequences in Germany. greater reduction of social contacts and perceived changes in everyday life were related to psychopathological symptoms. Subjectively perceived, but not officially announced stay-at-home orders are associated with mental health impairments. results do not support that public health measures per se are associated with mental health problems. Abstract: The COVID-19 pandemic is suggested to have a negative impact on mental health. To prevent the spread of Sars-CoV-2, governments worldwide have implemented different forms of public health measures ranging from physical distancing recommendations to stay-at-home orders, which have disrupted individuals' everyday life tremendously. However, evidence on the associations of the COVID-19 pandemic and public health measures with mental health are limited so far. In this study, we investigated the role of sociodemographic and COVID-19 related factors for immediate mental health consequences in a nationwide community sample of adults from Germany ( N  = 4335). Specifically, we examined the effects of different forms and levels of restriction resulting from public health measures (e.g. quarantine, stay-at-home order) on anxiety and depression symptomatology, health anxiety, loneliness, the occurrence of fearful spells, psychosocial distress and life-satisfaction. We found that higher restrictions due to lockdown measures, a greater reduction of social contacts and greater perceived changes in life were associated with higher mental health impairments. Importantly, a subjectively assumed but not an officially announced stay-at-home order was associated with poorer mental health. Our findings underscore the importance of adequate risk communication and targeted mental health recommendations especially for vulnerable groups during these challenging times.